أثر الفكر الحنيفي في مجتمع الجزيرة العربية قبل الاسلام - عبد الحميد شيماء فاضل; محمد صدام جاسم (Al-Adab Journal, 2019)
peace be upon him based on Tawheed, and the owners of the Hanifiyyah are the monotheists who are characterized as the Prophet Ibrahim peace be upon him. The aim of this research is to clarify the historical period that the Arabs lived in the pre-Islamic society between the call of Abrahamic Hanifa, the period of its cessation and the disappearance of its objectives and teachings and the turning of the Arabs in their thought to idolatry and the reasons for this intellectual transformation. In Paganism, this call was led by a number of enlightened enlightened intellectuals, who uphold the teachings of our prophet Ibrahim (peace be upon him) calling for the oneness of God and the rejection of idolatry and idolatry.